Genealogi Larangan Sasuku: Menelusuri Akar Fikih dan Filosofi Adat dalam Perkawinan Minangkabau - Junidar Sartika; Asfar Hamidi Siregar (Jurnal Pustaka Cendekia Pendidikan, 2025)
This research is motivated by the existence of Minangkabau customs which have a tradition of prohibiting marriage within the same tribe. This means that in Minangkabau customs it is forbidden for a man to have the same tribe as a woman he wants to marry. Interestingly, there is no verse in the Qur'an or Hadith regarding this marriage within the same tribe, while Minangkabau customs adhere to the principle commonly known by its proverb, namely "Adaik basandi syarak, syarak basandi Kitabullah". Therefore, this study aims to analyze the tradition of prohibiting marriage within the same tribe in Minangkabau, by focusing on the study of the principles and factors causing the prohibition of marriage within the same tribe in Minangkabau, as well as its analysis according to customary law and Islamic law. The method used is library research with a normative approach, where the data obtained is analyzed qualitatively. The results of the study show that the Minangkabau community adheres to an exogamous marriage system, which means that someone from a certain tribe must marry someone from another tribe. The prohibition of marriage within the same tribe in Minangkabau is also due to the implications of the matrilineal customary system or maternal lineage. This is because there are principles and thoughts that view inter-tribal marriage as a form of family or very close kinship, which if implemented will narrow family ties, as a pioneer of the destruction of the tribe, and produce low-quality offspring. Therefore, someone from Minangkabau is required to marry someone from outside their tribe to maintain unity and harmony in their society. According to the logic of Minangkabau customary law, inter-tribal marriage is considered bad and can be subject to moral sanctions. The prohibition of inter-tribal marriage in Minangkabau is included in the category of 'urf sahih, this prohibition is also not considered haram according to sharia because it is in accordance with the maqashid sharia regarding the maintenance of offspring so as not to produce weak offspring.